DEFINING STAGE FOR DEVELOPMENT OF STUDENT WORKSHEETS ORIENTED TO HIGHER ORDER THINKING SKILLS IN HIGH SCHOOL - Alfi Fadhilah Juneri; Rahmadhani Fitri; Mila Karmila (Universitas Negeri Padang, 2022)
The 2013 curriculum requires students to be able to think at a higher level or High Order Thinking Skill (HOTS). HOTS is a thinking ability that not only requires the ability to remember, but also requires other higher skills, such as critical thinking skills, problem solving, and decision making. HOTS is very much needed in the world of education, especially in learning biology. One of the teaching materials that can be used to train students' HOTS is the student worksheet. The purpose of this study was to find data at the stage of defining high-order thinking skill-oriented student worksheet. The sampling technique was observation, interviews and questionnaires to teachers and students of SMAS Adabiah Padang. The results showed that the teaching materials available at SMAS Adabiah Padang and already used the 2013 Curriculum, but this worksheet used had not been able to train students' high-level thinking skills. Based on the results of interviews with students that 94% of students agree to develop worksheet-oriented. Therefore, it is necessary to develop HOTS-oriented worksheets to train students' higher-order thinking skills.